Impact of off-farm income on food security and nutrition in Nigeria - Raphael O. Babatunde; Matin Qaim (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
While the poverty implications of off-farm income have been analyzed in different developing countries, much less is known about the impact of off-farm income on household food security and nutrition. Here, this research gap is addressed by using farm survey data from Nigeria. Econometric analyses are employed to examine the mechanisms through which off-farm income affects household calorie and micronutrient supply, dietary quality, and child anthropometry. We find that off-farm income has a positive net effect on food security and nutrition. The prevalence of child stunting, underweight, and wasting is lower in households with off-farm income than in households without. Using a structural model, we also show that off-farm income contributes to higher food production and farm income by easing capital constraints, thus improving household welfare in multiple ways.
Keywords: 330; Farm households; Food security; Micronutrients; Off-farm income